(untitled) (Universal International Scientific Journal, 2026)
This article analyzes the issues of applying scientific research conducted in the social and humanitarian sciences to practice using the example of the field of philology. In particular, the essence of the concept of "happiness" in literary literature, its philosophical, cultural and linguistic interpretations, and the possibilities of its application in the educational process are highlighted. The study used conceptual analysis, interpretative and comparative methods. The mechanisms for implementing scientific results into practice through innovative pedagogical approaches are substantiated.